Pembangunan Sistem Informasi Rekam Medis Ramdani Skincare & Spa Malang dengan Metode Prototyping berbasis Web - Cindy Cunday Cicimby; Denny Sagita Rusdianto; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
The medical record information system is a system that facilitates the service, recording and archiving of patient personal data in a health service in order to reduce errors that often occur. Ramdani Skincare & Spa is one of the beauty clinics in Malang City, the management of medical records at this beauty clinic is held by the Admin which includes inputting patient registration data, collecting patient history data and sending reports to the main director. Several problems were found in the medical record management process at Ramdani Skincare & Spa which was done manually using hardcopy, causing ineffective patient data archiving and the absence of continuity of patient visit history. Another problem that arises is that the service process from registration to clinical reporting is very slow, this triggers customer dissatisfaction. From the problems, a web-based application was made so that the management of medical records runsquickly, precisely and accurately. System development at Ramdani Skincare & Spa Malang using the prototyping method. System development includes the stages of needs analysis, implementation, and testing. The requirements analysis stage gets 82 functional requirements obtained from 1 iteration. Implementation stage uses PHP programming language CodeIgniter framework. Testing stages include functional and non-functional testing. Functional testing includes unit testing that successfullly performs a test path basedon 3 test cases and validation testing produces 100% valid from 73 cases. Non-functional testing using compatibility results can be accepted by users and can runwell on the browser.